EFEKTIVITAS UU NOMOR 16 TAHUN 2019 DALAM PENCEGAHAN PERNIKAHAN DI BAWAH UMUR DI KUA KECAMATAN KARANGANYAR TAHUN 2018-2023 - Hafshoh, H; Wibowo, Muhammad Kurniawan Budi; Pradana, Aditya Fajri Kurnia (Institut Islam Mamba'ul 'Ulum Surakarta, 2025)
underage marriage is still a significant problem in Indonesia, even though the minimum age for marriage has been raised to 19 years through the enactment of Law Number 16 of 2019. This study aims to evaluate how effective the regulation is in preventing underage marriage at the Religious Affairs Office (KUA) of Karanganyar District in the period 2018-2023. This ressearch will use a descriptive qualitative method with the type of empirical legal research, data collection through interview techniques, observation and document studies. The results of the study show a decrease in the number of underage marriages from 2022 to 2023, but environmental, social, cultural and educational factors are still the main obstacles in implementing the regulation. New findings from this study indicate that from the implementation of the Law, the number of permits at the Religious Courts is higher because the minimum age for marriage has been increased.